2020
DOI: 10.1101/2020.02.05.936294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic immune-modulation by Histone Deacetylase Activity (HDAC) of tissue and organ regeneration inXenopus laevis

Abstract: In the present work we propose to shed light on the epigenetic control of immune mechanisms involved during Xenopus tail regeneration. Here we show that the first 24 hour post amputation (hpa), which exclusively encompasses the first wave of myeloid differentiation, are crucial to epigenetically modulate the regenerative ability of Xenopus tadpoles. During this developmental window, HDAC activity was shown to be necessary for the proper establishment of myeloid cells dynamics in the regenerative bud, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…HDAC action is required to properly establish two inflammatory genes, mpox and spib , whose pattern of expression produces an inflammatory response that is a key player during Xenopus tail regeneration [ 108 ]. Suzuki et al, also reported that Xenopus tail amputation induced ROS signaling, which was preceded by a rise in the level of H2K9ac, which contributed to the reactivation of regeneration genes ( shh, fgf20 ) in notochord regeneration and represented a signaling site for orchestrating tail formation ( Figure 1 B) ( Table 1 ) [ 106 ].…”
Section: Epigenetic Regulation Of Regeneration-competent Animals Afte...mentioning
confidence: 99%
“…HDAC action is required to properly establish two inflammatory genes, mpox and spib , whose pattern of expression produces an inflammatory response that is a key player during Xenopus tail regeneration [ 108 ]. Suzuki et al, also reported that Xenopus tail amputation induced ROS signaling, which was preceded by a rise in the level of H2K9ac, which contributed to the reactivation of regeneration genes ( shh, fgf20 ) in notochord regeneration and represented a signaling site for orchestrating tail formation ( Figure 1 B) ( Table 1 ) [ 106 ].…”
Section: Epigenetic Regulation Of Regeneration-competent Animals Afte...mentioning
confidence: 99%